Analysis User Satisfaction of XYZ Application with End User Computing Satisfaction Method and Delone and Mclean - Giansyah, Qhoiril Aldi; Maita, Idria; Megawati, Megawati; Salisah, Febi Nur (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2024)
Rapidly developing technology has made internet service providers such as XYZ provide an application which promises convenience for its consumers to make transactions to purchase credit, internet quota, and other services. this application is one of the fairly well-known providers and is currently competing with other providers. this provider targets young people because in terms of its products which are quite competitive with a wide reach and prices that are quite cheap for young people. Of course, customers will feel the convenience of transacting using the official service application. The convenience offered can make business processes more efficient and can be used to improve the quality of their services.This study uses the End User Computing Satisfaction model method and the Delone and Mclean model with 9 research variables (content, accuracy, format, ease of use, timeliness, system quality, information quality, and service quality, and security), The purpose of this study is to assess the effectiveness of the application..Out of the nine variables included in the research results, only two Service Quality and Accuracy have a statistically significant impact. The model provided in this study has a Rsquared score of 0.792, indicating a strong level of customer satisfaction.